INSTRUCTIONAL TECHNIQUES IN PARTIAL IMMERSION PROGRAM :A Case at a Junior High School in Bandung - Ratih Yuliantini, - (2008)
This study investigates instructional techniques applied by teachers in partial Immersion program in a Junior High School's setting. Getting an understanding of instructional techniques and materials employed by the teachers are the main objectives of this study, to be afterwards may become a model of other schools in applying the program. The data were gained from three times observation using audio-video recordings and field-note taking, interview and document investigation. The transcribed data from audio-video recordings were then analyzed using Snow's instructional technique. The transcribed data from interview is used as additional information for the study. While the data gained from document investigation is utilized to be a written prove of the teaching learning process. The findings of the study reveal that the teachers under investigation applied Snow's instructional techniques in providing students with comprehensible input. There are four main techniques applied by the teachers; modifying input, using contextual cues, checking for understanding and designing appropriate lessons. Besides, the teacher implements another technique named code switching but use incorrect grammaticality. Furthermore, the materials conveyed in the Immersion classroom are parallel to that of National Standard Curriculum with the additional four elements that have to be applied in the Immersion teaching learning process. This study concludes that the observed Immersion program is success in improving students' target language, academics achievement as well as cross cultural understanding.